2001
DOI: 10.1007/bf02982072
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Reactivation in a Patient With Chronic GVHD After Allogeneic Peripheral Blood Stem Cell Transplantation

Abstract: We report a patient with fatal hepatitis B virus (HBV) reactivation after treatment for chronic graft-versus-host disease (GVHD) following allogeneic peripheral blood stem cell transplantation to treat chronic myelogenous leukemia. The presence of antibodies to hepatitis B surface antigen (HBsAb) prior to transplantation indicated previous HBV infection. Liver damage first developed 8 months after transplantation with the disappearance of HBsAb. Hepatitis B antigen was first noted during an examination of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…21 HBV-associated liver disease after allo-HSCT is often temporary and not serious, but fatal liver damage has been reported in some cases. 16,18 In the three patients with reverse seroconversion reported herein, there was mild hepatitis in only one patient, followed by spontaneous clearance of HBsAg. The other two patients had no biochemical signs of liver damage but became chronic carriers with high-level HBV viraemia.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…21 HBV-associated liver disease after allo-HSCT is often temporary and not serious, but fatal liver damage has been reported in some cases. 16,18 In the three patients with reverse seroconversion reported herein, there was mild hepatitis in only one patient, followed by spontaneous clearance of HBsAg. The other two patients had no biochemical signs of liver damage but became chronic carriers with high-level HBV viraemia.…”
Section: Discussionmentioning
confidence: 84%
“…During early follow-up, they had low-level viraemia and there was a 2 log increase in HBV-DNA concentration starting 2-4 months prior to reverse seroconversion. Similarly, Sakamaki et al 18 reported one patient who was HBV-DNA positive by real-time PCR with 89 copies/ml serum (branched DNA assay negative) about 10 months after allo-HSCT. After an additional 12 months he developed fatal liver damage with reverse seroconversion and HBV-DNA concentrations of 2 Â 10 6 copies/ml.…”
Section: Discussionmentioning
confidence: 87%
“…[39][40][41][42][43][44][45][46][47][48][49][50] Based on reported series, 47,[51][52][53][54] the frequency of seroreversion ranges between 14% and 50% (Table 1A). The wide range reported could be explained by risk estimation based on small series, missed cases of seroreversion due to absence of symptoms, and variable duration of posttransplant follow-up.…”
Section: Reactivation Inmentioning
confidence: 99%
“…It was reported that two types of PBSCT, i.e., autologous PBSCT (auto-PBSCT) and allo-PBSCT, induce post-transplantation de novo hepatitis B. [14][15][16][17][18][19] Because immunosuppressive therapy is performed over a long period to suppress chronic GVHD particularly after allo-PBSCT, the transplantation potentially induces de novo hepatitis B at a higher incidence than auto-PBSCT and even after a long post-transplantation period. [14][15][16] Large-scale studies on de novo hepatitis B have been conducted recently and typical drugs that could induce HBV reactivation have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Because immunosuppressive therapy is performed over a long period to suppress chronic GVHD particularly after allo-PBSCT, the transplantation potentially induces de novo hepatitis B at a higher incidence than auto-PBSCT and even after a long post-transplantation period. [14][15][16] Large-scale studies on de novo hepatitis B have been conducted recently and typical drugs that could induce HBV reactivation have been identified. [13,20,21] In general, the immunosuppressants were categorized into low-, moderate-, or high-risk groups based on estimates of reactivation using available evidence.…”
Section: Discussionmentioning
confidence: 99%